Partisipasi Masyarakat Dalam Pembentukan Peraturan Desa di Desa Sukamantri Kecamatan Ciawi Kabupaten Tasikmalaya - Muhamad Yudia Noor Akbari; Erlan Suwarlan; Agus Nurulsyam (International Forum of Researchers and Lecturers, 2025)
This research is motivated by the low level of community participation in the process of forming Village Regulations in Sukamantri Village, Ciawi District, Tasikmalaya Regency, which has resulted in less than optimal public involvement in decision-making at the village level. The purpose of this study is to determine the extent of community participation in the formation of Village Regulations and to identify inhibiting factors and efforts made by the village government to increase such participation. This study uses a qualitative method with 11 informants consisting of village officials, community leaders, and villagers. Data were collected through literature studies, observations, in-depth interviews, and documentation. Data analysis was conducted qualitatively by processing information from interviews and observations to draw conclusions. The results of the study indicate that community participation in the formation of Village Regulations in Sukamantri Village is still not optimal. The main obstacles faced include limited implementation time which results in some community members being unable to attend official forums, low legal literacy and understanding of the importance of involvement in village policy formulation, ineffective mechanisms for conveying aspirations, and the dominance of certain figures in the decision-making process which limits the representation of all elements of society. To overcome these obstacles, the village government has undertaken various efforts, including expanding outreach through neighborhood associations (RT/RW) and social media, opening additional discussion forums at the hamlet level, and involving various community groups, including women and youth, in village meetings. These efforts are expected to increase community awareness, involvement, and satisfaction with the Village Regulation drafting process, so that in the future, Village Regulation drafting can be more transparent, inclusive, and able to accommodate the aspirations of all levels of society.